The Importance of Religion in the formation of Cultural Knowledge and Values (Eurasian Journal of Religious Studies, 2022)
In this article, we investigate the crossing point of religion and social values for maintainability. In any case, the degree to which they are deciphered into cultural demeanors and behavior changes agreeing to set. Contend that whereas there is much potential back for human values for maintainability inside devout conventions, it is fundamental that religion is seen as a complex, multi-dimensional regulation wonder. Subsequently, investigation of the relationship between religion and social values must account for the set of accounts, hones. Utilizing this focal point, we appear how devout viewpoints can contribute to operationalizing speculations of systemic alter for maintainability. At long last, we lay out key standards for assist maintainability inquire about looking for to progress information on the relationship between religion and cultural values. The comes about bolster a dissociative continuum which incorporates not as it was related separation, but moreover wholeness related to concepts of extended awareness. Within the process of social investigation, ready to recognize particular components of a specific culture, patterns that incorporate the potential of the devout character. The controls the issue of social personality in terms of its specifics.Key words: сulture, value, identification, factor, cultural research
Keywords: Сulture; Value; Identification; Factor; Cultural Research